Vehicles as outdoor BFR sources: Evidence from an investigation of BFR occurrence in road dust. (July 2017) - Cao, Zhiguo; Zhao, Leicheng; Kuang, Jiangmeng; Chen, Qiaoying; Zhu, Guifen; Zhang, Kunlun; Wang, Shihua; Wu, Peipei; Zhang, Xin; Wang, Xuefeng; Harrad, Stuart; Sun, Jianhui
Abstract: The distribution of brominated flame retardants (BFRs) including ∑8 PBDEs, DBDPE, BTBPE, EH-TBB, BEH-TEBP and PBEB in road dust (RD) collected in Xinxiang, China was characterized. Analysis of RD samples indicated that the BFR abundance declined as traffic density decreased, with total mean levels of 292, 184, 163, 104 and 70 ng g −1 dust at sites from traffic intersections, main roads, collector streets, bypasses and parks, respectively. A possible explanation for this phenomenon is that the majority of BFRs may be emitted from the interior of vehicles via their ventilation systems. Of the 13 analyzed substances, BDE-209 and BEH-TEBP were the most abundant components in RD from Xinxiang. Similar amounts of ∑BDEs excluding BDE-209 were found at different types of sampling sites, and thus, atmospheric deposition is also a probable source of BFRs in RD which can be subject to air transportation. The main PBDE sources were traced to commercial products including DE-71, Bromkal 79-8DE, Saytex 201E and Bromkal 82 DE mixtures. Our results confirm that the use of deca-BDE commercial mixture is a major source of PBDE contamination in RD. Risk assessment indicated the concentrations of BFRs in RD in this study do not constitute a non-cancer or cancer risk to humans through ingestion. Annual emission fluxes of the commonly detected BFRs via RD in China were estimated to be up to 4980 kg year −1 . Graphical abstract: Highlights: BDE-209 and BEH-TEBP dominated in the road dust samples. BFR abundance in road dust declined as traffic density increased. Traffic was deduced to be an important outdoor emission source of BFRs. BFRs associated with road dust in China were estimated up to be 4980 kg year −1 .